ETNOMATEMATIKA PADA AKTIVITAS PEMBUATAN BATIK MOTIF TEMBAKAU DI RUMAH PRODUKSI BATIK NHORA PENGESTU AMBULU SEBAGAI BAHAN PAKET SOAL TES - Cahyanti, Endah Dwi (Department of Mathematics Education , University of Jember, 2020)
Ethnomatematics is the science of mathematics practiced by a cultural group where the society has unconsciously applied the concept of mathematics. The purpose of this study is to describe ethnomatemics in the activity of making tobacco motifs and to produce test packages. This type of research is a qualitative research with an ethnographic approach. There are three subjects in this study, S1 as the maker of patterns / designs, color locking, and